Effect of Probiotics in Stress-Associated Constipation Model in Zebrafish (Danio rerio) Larvae - Lee, Ayoung; Kim, Seung Young; Kang, Seyoung; Kang, Seong Hee; Kim, Dong Woo; Choe, Jung Wan; Hyun, Jong Jin; Jung, Sung Woo; Jung, Young Kul; Koo, Ja Seol; Yim, Hyung Joon; Kim, Suhyun (International Journal of Molecular Sciences, 2024)
The pathophysiology of functional bowel disorders is complex, involving disruptions in gut motility, visceral hypersensitivity, gut–brain–microbiota interactions, and psychosocial factors. Light pollution, as an environmental stressor, has been associated with disruptions in circadian rhythms and the aggravation of stress-related conditions. In this study, we investigated the effects of environmental stress, particularly continuous light exposure, on intestinal motility and inflammation using zebrafish larvae as a model system. We also evaluated the efficacy of probiotics, specifically Bifidobacterium longum (B. longum), at alleviating stress-induced constipation. Our results showed that continuous light exposure in zebrafish larvae increased the cortisol levels and reduced the intestinal motility, establishing a stress-induced-constipation model. We observed increased inflammatory markers and decreased intestinal neural activity in response to stress. Furthermore, the expressions of aquaporins and vasoactive intestinal peptide, crucial for regulating water transport and intestinal motility, were altered in the light-induced constipation model. Administration of probiotics, specifically B. longum, ameliorated the stress-induced constipation by reducing the cortisol levels, modulating the intestinal inflammation, and restoring the intestinal motility and neural activity. These findings highlight the potential of probiotics to modulate the gut–brain axis and alleviate stress-induced constipation. Therefore, this study provides a valuable understanding of the complex interplay among environmental stressors, gut function, and potential therapeutic strategies.